O ensino de polinômios e gráficos na educação básica - Sato, Humberto Domingues Thiago (Universidade Federal de São Carlos, 2019)
In this monography, we study polynomial functions, starting with a brief historical research about how the general solutions of the first to third degree polynomial equations were constructed, then we proceed to analyze the important points that the National Curricular Parameters stand out in relation to the teachings of algebra and polynomials. In the development of the work, we also address the demonstrations of the Fundamental Theorem of Algebra (analytic and algebraic proofs) and the demonstrations of the general solutions of the polynomial equations up to degree three by means of radicals. Finally, some activities are introduced to be applied in the classroom in order to improve the teaching and learning process through Geogebra computational software. We apply one of these activities in a classroom and we discuss the results.
The teaching of polynomials and graphics in the elementary school
Keywords: Polinômios; Equações polinomiais; Funções polinomiais; Ensino de polinômios; CIENCIAS EXATAS E DA TERRA::MATEMATICA::ALGEBRA